Infant and adolescent deaths in Istanbul due to home accidents - Aşirdizer, Mahmut; Yavuz, Mehmet Sunay; Albek, Emre; Cantürk, Gürol (The Turkish Journal of Pediatrics, 2005)
Adolescent and infant deaths due to home accidents pose an important social problem and can be prevented significantly by appropriate measures. The aims of this study about adolescent deaths under the age of 18 and infant deaths due to home accidents were assessment of risk factors and proposals for protective measures. Toward these aims, 414 autopsy reports (Provided by Mortuary Section, Council of Forensic Medicine, Istanbul Turkey, 1996-2000) were reviewed, as well as scene investigation data and information from eyewitnesses. Determination of risk factors, appropriate education, as well as legal regulations for manufacturers of household articles may significantly reduce the number of infant and adolescent deaths due to home accidents.